Development of a Parental Role Instrument in Academic Achievement among Eleventh-Grade Students at SMAN 10 Takengon - Cindy Annisa; Syarifah Ainy Rambe; Yoga Temasmiko (Insight: Journal of Counseling and Psychology, 2026)
This study aims to develop a valid and reliable instrument to measure the role of parents as mentors, motivators, and facilitators in supporting the academic achievement of 11th-grade students at SMAN 10 Takengon. Parental involvement is widely recognized as a crucial factor influencing students’ learning outcomes, particularly during adolescence when academic motivation may decline. The research employed a Research and Development (R&D) method, adapted from the Borg & Gall model. The development process included theoretical analysis, indicator formulation, expert validation, and limited trials on a student sample. The validation results indicated that the instrument meets content validity standards, while the reliability test yielded a Cronbach’s Alpha of 0.87, indicating good internal consistency. This instrument is expected to help schools and researchers identify the extent of parental involvement in academic success through three main dimensions: learning guidance, motivational support, and the provision of learning facilities.